2020
DOI: 10.21037/qims.2019.12.01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the LHPP gene polymorphism on the functional and structural changes of gray matter in major depressive disorder

Abstract: Background: A single-nucleotide polymorphism (SNP) of the LHPP gene (rs35936514) has been reported to be associated with major depressive disorder (MDD) in genome-wide association studies. However, the systems-level neural effects of rs35936514 that mediate the association are unknown. We hypothesized that variations in rs35936514 would be associated with structural and functional changes in gray matter (GM) at rest in MDD patients.Methods: A total of 50 MDD patients and 113 healthy controls (HCs) were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Besides mood changes, depression is also associated with widespread reductions in gray matter in regions including the DLPFC 14 , 15 , 40 , cingulate cortex (including the anterior 14 , 15 , 41 , posterior 40 , 41 and subgenual 42 cingulate cortices), hippocampus, thalamus, and amygdala 14 , 15 , 26 , 43 . Our primary analysis indicated that HD tDCS treatment induces significant gray matter increases at the left DLPFC brain region.…”
Section: Discussionmentioning
confidence: 99%
“…Besides mood changes, depression is also associated with widespread reductions in gray matter in regions including the DLPFC 14 , 15 , 40 , cingulate cortex (including the anterior 14 , 15 , 41 , posterior 40 , 41 and subgenual 42 cingulate cortices), hippocampus, thalamus, and amygdala 14 , 15 , 26 , 43 . Our primary analysis indicated that HD tDCS treatment induces significant gray matter increases at the left DLPFC brain region.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Search according to NCBI conserved domain database (CDD) ( https://www.ncbi.nlm.nih.gov/cdd ), HDHD2 belongs to the HAD-like hydrolase superfamily structurally and is found to be similar to phospholysine phosphohistidine inorganic pyrophosphate phosphatase ( LHPP ), which is known to associated with depression. 56 Sleep abnormalities are one of the critical symptoms of depression. 57 However, its function is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Based on GWAS studies, LHPP. has also been implicated in major depressive disorders [133][134][135], alcohol dependence, and risky behavior [136]. A confirmed substrate for LHPP.…”
Section: Histidine Phosphatasesmentioning
confidence: 93%